Providing A Novel Distributed Method For Energy Management In Wireless Sensor Networks Based On The Node Importance Criteria (Journal of Namibian Studies : History Politics Culture, 2023)
Energy management in wireless sensor networks has great importance. In these networks, sensor nodes typically operate on batteries and due to limited energy resources, energy management is crucial for optimal performance and battery lifetime of these nodes. The use of suitable energy management algorithms in wireless sensor networks can help improve network efficiency and increase the battery life of sensor nodes. In this paper, a new method is proposed for optimal energy consumption management in wireless sensor networks. In the proposed method, each node selects a cluster for itself in a distributed manner or chooses itself as the cluster head. This method is designed based on the importance of nodes. The proposed method was implemented in different scenarios for wireless sensor networks such as sparse and dense wireless sensor networks. In all simulations, the proposed method demonstrated good capabilities in optimal energy consumption management.